2020
DOI: 10.20944/preprints202007.0142.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19: The Rollercoaster of Fibrin(ogen), D-dimer, von Willebrand Factor, P-selectin and Their Interactions with Endothelial Cells, Platelets and Erythrocytes

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2), coronavirus disease 2019 (COVID-19)-induced infection is strongly associated with various coagulopathies that may result in either bleeding and thrombocytopenia or hypercoagulation and thrombosis. Thrombotic and bleeding or thrombotic pathologies are significant accompaniments to acute respiratory syndrome and lung complications in COVID-19. Thrombotic events and bleeding, often occurs in subjects with weak multiple risk factors and co-morbi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 137 publications
2
107
2
1
Order By: Relevance
“…Strongly bound up with the coagulopathies accompanying severe COVID-19 disease is the presence of hyperferritinaemia (in cases such as the present it is a cell damage marker (28)) and a cytokine storm, (29)(30)(31)(32)(33) which usually occurs in the later phase of the disease (16). Excess iron has long been known to cause blood to clot into an anomalous form (34), later shown to be amyloid in nature (18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Strongly bound up with the coagulopathies accompanying severe COVID-19 disease is the presence of hyperferritinaemia (in cases such as the present it is a cell damage marker (28)) and a cytokine storm, (29)(30)(31)(32)(33) which usually occurs in the later phase of the disease (16). Excess iron has long been known to cause blood to clot into an anomalous form (34), later shown to be amyloid in nature (18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the possibility of thromboembolic disorders in this group of patients, a thrombotic episode in a patient with mild VWF disease [ 19 ] and the possibility of bleeding associated with SARS-CoV-2 infection [ 20 ] have all been reported. All the while there is a discussion about a possible association between complications and the level of factor VWF [ 21 , 22 ]. It has also been shown that the incidence of concomitant diseases has an impact on the severity and mortality of COVID-19 [ 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature suggests the possibility of thromboembolic disorders, also in patients with CBD [ 19 ]. There are known cases of bleeding related to COVID-19 infection [ 20 ] and also the influence of VWF factor level on the risk of complications is discussed [ 21 , 22 ]. The aim of this article is to give recommendations to doctors and dentists for the optimal management of patients with CBD during the SARS-CoV-2 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in RBC aggregation also accompany cardiovascular diseases such as arterial hypertension [ 17 , 18 ], atherosclerosis [ 19 ], cardiac infarction, and ischemia [ 20 ], as well as during metabolic disorders such as diabetes mellitus [ 21 , 22 ]. During COVID-19 infection, pathological levels of fibrin and fibrinogen result in elevated membrane fragility and the pathological elasticity of erythrocytes [ 23 ]. Therefore, a complex study of the interaction between fibrinogen molecules and RBC will allow developing new approaches of the targeted treatment of hemorheological disfunctions caused by an evaluated fibrinogen-induced aggregation of RBC.…”
Section: Introductionmentioning
confidence: 99%